(untitled) (Research, Society and Development, 2022)
Due to technological advances in our society, the use of digital technologies is gaining more and more space in debates and discussions in the educational context. However, teachers have difficulties in enjoying all the potential they have to offer. In view of this fact, this paper brings a Systematic Literature Review (RSL) about the potentialities and difficulties of the use of digital technologies in teaching practice by mathematics teachers. The research was based on two databases (Google Scholar and Periódico Capes), searching for articles in Portuguese from 2017 to 2020. According to the results obtained, it is noted that all studies highlight the importance of the insertion of digital educational technologies in teaching practice, due to its high potential to instigate students to construct knowledge, working the objects of knowledge in a technological and significant way. However, there is no initial and continued training on classroom use, in addition to the limitation of resources/equipment available in schools.